PENGARUH LEVERAGE DAN UKURAN PERUSAHAAN PADA EARNINGS RESPONSE COEFFICIENT - Kusuma Dewi, Anak Agung Puteri; Dwiana Putra, I Made Pande (E-Jurnal Akuntansi, 2017)
Earnings quality is important for investors who use financial statements for purposes of the contract and investment decision making. This study aimed to investigate the effect of leverage and the size of the company on earnings quality is measured using the Earnings Response Coefficients. This study was performed on companies listed in Indonesia Stock Exchange 2009-2013 period. The cornerstone of the theory used is the signal theory. The population in this research is manufacturing companies listed in Indonesia Stock Exchange from 2009 to 2013 year. Samples were determined using purposive sampling method. The number of the selected sample are 42 companies. Data analysis method used is multiple linear regression analysis. Based on the analysis that has been done, this study proves that the size of the company's leverage have negative effect on earnings response coefficients.
Keywords: leverage; firm size; cummulative abnormal return; unexpected earnings; earnings response coefficient